Authenticity testing of environment-friendly Korean rice (Oryza sativa L.) using carbon and nitrogen stable isotope ratio analysis. (1st November 2017) - Chung, Ill-Min; Park, Sung-Kyu; Lee, Kyoung-Jin; An, Min-Jeong; Lee, Ji-Hee; Oh, Yong-Taek; Kim, Seung-Hyun
Highlights: δ 13 C and δ 15 N in rice samples change as a function of cultivation conditions. δ 13 C and δ 15 N allow discrimination of environment-friendly and conventional rice. δ 15 N is more useful than δ 13 C for discrimination of environment-friendly rice. Two-dimensional δ 13 C/δ 15 N plots facilitate authentication of organic rice. Conventional and environment-friendly rice samples lack pesticide residues. Abstract: The increasing demand for organic foods creates, in turn, a pressing need for the development of more accurate tools for the authentication of organic food in order to ensure both fair trade and food safety. This study examines the feasibility of δ 13 C and δ 15 N analyses as potential tools for authentication of environment-friendly rice sold in Korea. δ 13 C and δ 15 N examination in different rice grains showed that environment-friendly rice can be successfully distinguished from conventional rice. No multi-residue pesticides were detected in the examined rice samples, including conventional rice. This study demonstrates the complementary feasibility of δ 13 C and δ 15 N analyses for the authentication of environment-friendly rice sold in Korea in cases where pesticide residue analysis alone is insufficient for discrimination of organic and conventional rice. In future, complementary analyses including compound-specific isotope ratio analysis might be employed for improving the reliability of organic authentication.